ECONOMICS OF FEEDING UNDER VARYING LEVELS OF DRIED DISTILLERS GRAINS IN TELLICHERRY KIDS - P. Arun Nehru; P. Tensingh Gnanaraj; Thanga Tamil Vanan; L. Radhakrishnan; S. Meenakshi Sundaram; P. Pothiappan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A trial was conducted to assess the post weaning growth performance of Tellicherry kids by feeding varying levels of dried distillers grains (DDG) in an organized goat farm, Chennai. Thirty six numbers of early weaned Tellicherry male kids aged around2 months were randomly selected and allotted to four groups. Each group consisted of nine kids and all animals were reared under similar intensive system of management. The kids were fed with concentrate and roughage in a ratio of 60:40 based on 4 per cent body weight. Pigeon pea (Cajanus cajan) straw was used as a sole source of roughage. The concentrate mixture contained varying levels of dried distillers grains (0, 5, 10 and 15 per cent) and other ingredients. Body weight and body measurements were taken once in fortnight. Economics was calculated on using this DDG. The dry matter intake and feed conversion ratio showed no significant difference between the study groups. The cost per kg weight gain for the diets containing 0, 5, 10 and 15 per cent dried distillers grains was Rs. 191.48, Rs. 176.80, Rs. 155.35 and Rs. 138.95 respectively. In the respective treatment groups, the net return per animal was Rs. 350.11, Rs. 570.78, Rs. 953.51 and Rs. 1327.42 respectively.